Designing an E-Shop as a Promotional Medium for MSME Products at Azis Furniture Using the OpenCart Platform - Faisal Hidayat; Alifur Rahman; M. Muhfa Rizal (Program Studi Bisnis Digital - Fakultas Ekonomi dan Bisnis Islam, 2025)
The advancement of information technology provides significant opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their marketing reach through Digital media. However, Azis Perabot, an MSME engaged in furniture sales, faces challenges in expanding its promotional reach due to its reliance on traditional marketing methods, which are limited in scope. This study aims to design and implement an E-Shop using the OpenCart platform as a promotional medium to address these issues and enhance product visibility online. The research applies the Research and Development (R&D) method supported by a qualitative descriptive approach to analyze needs, develop solutions, and evaluate the resulting prototype. The development model used is ADDIE. The research process includes business needs analysis, system design, implementation of key E-Shop features, and prototype testing to ensure its functionality. The OpenCart platform was chosen for its flexibility, ease of use, and support for adequate e-commerce features. The result of this study is a prototype E-Shop that serves as a Digital product catalog, facilitates product management, and enhances customer accessibility in selecting and purchasing products. However, this E-Shop is still limited to offline implementation and has not yet been uploaded to a wider online network. These findings represent a significant first step in digitizing MSMEs to improve promotional efficiency and competitiveness in the rapidly growing Digital era. Future researchers are expected to continue developing this project by integrating the E-Shop into the online network, testing its application in real-world scenarios, and evaluating its impact on sales and promotions for Azis Perabot. This research is expected to provide valuable contributions to advancing Digital transformation for MSMEs in Indonesia and serve as a reference for other MSMEs to utilize technology to expand their markets. With these steps, it is hoped that more MSMEs will be able to leverage technology to grow and compete in an increasingly competitive global market.